PENGARUH KREATIVITAS PRODUK TERHADAP PENINGKATAN VOLUME PENJUALAN DI CV. OKEY TEHNIK BANDUNG - DIAN CANDRA FATIHAH DIAN CANDRA FATIHAH; CHANDRA FIRMANSYAH CHANDRA FIRMANSYAH (EKBIS (Ekonomi & Bisnis), 2019)
This study aims to find out the effect of product creativity on increasing sales volume in CV. Okey Tehnik. The research method which used a quantitative method with techniques of data collection used by means observation, interviews and questionnaires that have relation with the primary issue, and to see the relation two variables used test analysis techniques validity of data, reliability test, simple linear regression analysis, correlation analysis, the coefficient of determination. The results showed that there was a significant influence between product creativity on increased sales volume in CV. Okey Tehnik of 35.4% and 64.4% were influenced by other factors. This showed that the hypothesis was proven to be a positive influence between product creativity and sales volume. The advice that can be given is that there are a number of employees targeted to succeed punctual and maximum. And also need additional facilities or production equipment and expansion of production sites to be more comfortable.